When is FDI a Capital Flow? - Dalia Marin; Monika Schnitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper we analyze the conditions under which a foreign direct investment (FDI) involves a net capital flow across countries. Frequently, foreign direct investment is financed in the host country without an international capital movement. We develop a model in which the optimal choice of financing an international investment trades off the relative costs and benefits associated with the allocation and effectiveness of control rights resulting from the financing decision. We find that the financing choice is driven by managerial incentive problems and that FDI involves an international capital flow when these problems are not too large. Our results are consistent with data from a survey on German and Austrian investments in Eastern Europe.
urn:nbn:de:bvb:19-epub-13425-0
Keywords: F23; F21; G32; L20; D23; 330; Multinational firms; Firm specific capital costs; Internal capital markets; International capital flows